Silicon-modified Solidago canadensis L. biochar suppresses soilborne disease and improves soil quality - Sheng Wang; Abdul Hafeez; Tiantian Zhang; Muhammad Junaid Rao; Sicong Li; Kunzheng Cai (Biochar)
Abstract Nowadays, biochar is well recognized for its multiple promising effects on the soil quality and plant health. However, there are limited studies on the utilization of invasive plants for biochar production. In the present study, silicon (Si)-modified biochar was synthesized from Solidago canadensis L., an invasive alien plant in southern China, at different pyrolysis temperatures (450, 550, and 650 ℃). The role of biochar in controlling bacterial wilt, improving soil quality and plant health was assessed. The results revealed that Si-modified biochar had higher wilt suppressive effects than unmodified biochar. Si-modified biochar synthesized at 450 ℃ was found to be the most effective in reducing the abundance of R. solanacearum in soil (66.0%) and the incidence rate of bacterial wilt (59.1%). The Si-modified biochar increased soil available Si (58.2%–147.8%), C/N ratio (85.8–105.0%), and cation exchange capacity (19.7–54.5%). Additionally, it also enhanced the abundance of beneficial bacteria in the soil, such as Bacillus (341.7%), Streptomyces (222.0%), Gaiellales (255.4%), and Gaiella (133.3%). These findings suggest that Si-modified biochar derived from the invasive plant Solidago canadensis L. holds promise as a soil additive for disease control. Graphical Abstract